ADAKSI sebagai Gerakan Kesejahteraan Dosen ASN Indonesia: Narrative Inquiry - Yulita Sirinti Pongtambing; Esther Sanda Manapa (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to reconstruct the narrative of the establishment and struggle of the Aliansi Dosen ASN Kemdiktisaintek Seluruh Indonesia (ADAKSI), a collective movement advocating for the welfare of civil servant lecturers (ASN), particularly concerning the delayed disbursement of performance allowances (tukin). Using a narrative inquiry approach, this research traces digital records and real-world actions taken by ASN lecturers across Indonesia, including a symbolic flower board protest in January 2025, an audience with the Minister of Higher Education, Science, and Technology, and the organization of the first National Congress (MUNAS I ADAKSI) in May 2025. These narratives are analyzed as expressions of shared grievances, solidarity, and the formation of a collective identity among ASN lecturers who have long lacked institutional representation through official bodies like KORPRI. The findings reveal that ADAKSI functions not only as an advocacy platform for welfare but also as a socio-professional movement driven by intellectual ethics in demanding structural justice. Its actions, demands, and outcomes from MUNAS I mark a significant transition from fragmented protests to an organized national consolidation. The study recommends that policymakers create more inclusive spaces for dialogue with ASN lecturers and formally recognize independent professional organizations as strategic partners in the reform of Indonesia’s higher education system.